Highly Efficient and Super Stable Full‐Color Quantum Dots Light‐Emitting Diodes with Solution‐Processed All‐Inorganic Charge Transport Layers. Issue 12 (3rd March 2021) - Wang, Fuzhi; Wang, Zhenye; Zhu, Xiaodong; Bai, Yiming; Yang, Yun; Hu, Siqian; Liu, Yuqing; You, Baogui; Wang, Jun; Li, Yang; Tan, Zhan'ao
Abstract: High performance and super stable all‐inorganic full‐color quantum dot light‐emitting diodes (QLEDs) are constructed by adopting solution‐processed Mg‐doped NiO x (Mg‐NiO x ) nanoparticles as hole transport layer (HTL) and Al‐doped ZnO (AZO) as electron transport layer (ETL). Mg‐NiO x nanoparticles possess the advantages of low‐temperature solution processability, intrinsic stability, and controllable electronic properties. UV‐ozone (UVO) treatment is applied to the Mg‐NiO x film to modulate its surface composition. By carefully controlling the UVO treating time, favorable energy levels can be achieved to minimize the energy barrier for hole injection. At the cathode side, Al‐doping can reduce the conductivity of ZnO ETL and decrease the interface charge transfer, effectively, thus leading to more balanced charge injection and consequent high luminance and efficiency. The maximum luminance and EQE can reach as high as 38 444 cd m −2 and 5.09% for R‐QLEDs, 177 825 cd m −2 and 10.1% for G‐QLEDs, and 3103 cd m −2 and 2.19% for B‐QLEDs. The luminance values are the highest ever reported for all‐inorganic QLEDs. Furthermore, the all‐inorganic devices show much better resistance to water and oxygen existing in air. The results show that the ion‐doped NiO x and AZO nanoparticles would facilitate the design and development of highly efficient and super stable QLEDs. Abstract : High performance all‐inorganic quantum dot light‐emitting diodes (QLEDs) are fabricated by using solution‐processed Mg‐doped NiO x and Al‐doped ZnO nanoparticles as charge transport layers. Favorable energy levels and balanced charges lead to high luminance of 38 444, 177 825, and 3103 cd m −2 for red, green, and blue QLEDs, respectively, which are the highest values ever reported for all‐inorganic QLEDs.